Burnout and substance use in collegiate athletic trainers - Oglesby, L. W.; Gallucci, A. R.; Wynveen, C. J.; Ylitalo, K. R.; Benson, N. F. (Journal of Athletic Training, 2020)
Context: The Smith Cognitive-Affective Model of Athletic Burnout suggests that athletic trainers (ATs) suffering from burnout may engage in substance use as a coping behavior. Increases in self-reported burnout symptoms are often associated with increases in heavy episodic drinking and tobacco use among various health care providers. However, this relationship has not been examined thoroughly. Objective: To investigate the prevalence of substance use in ATs and identify relationships between symptoms of burnout and substance use among ATs. Design: Cross-sectional study. Setting: Web-based survey. Patients or Other Participants: A total of 783 certified ATs working full time in the collegiate or university setting were sampled for this study. Graduate assistant and other part-time ATs were excluded. The survey was distributed via the National Athletic Trainers' Association membership directory e-mail broadcast service. Main Outcome Measure(s): A 100-item online questionnaire consisting of items from previously used scales was used for this study. The survey included the Maslach Burnout Inventory and questions on substance use from the Monitoring the Future study. Multiple regression analyses were performed to analyze the survey data. All independent (Maslach Burnout Inventory subscales) and dependent (use of alcohol, tobacco, and marijuana) variables were mapped to the Smith Cognitive-Affective Model of Athletic Burnout to determine which dimensions of burnout altered the odds of self-reported substance use. Results: Almost half (46.3%) of participants admitted to at least 1 binge-drinking episode. However, the use of cigarettes, smokeless tobacco, marijuana, and energy drinks during the previous month was less pronounced in the sample. Emotional exhaustion (B = 0.008, P = .023) and personal accomplishment (B = -0.016, P = .02) were significantly correlated with binge drinking. Emotional exhaustion (Exp[B] = 1.017, P < .001) was also significantly positively correlated with energy-drink consumption. Conclusions: Some ATs engaged in heavy episodic drinking. Emotional exhaustion and a decreased sense of personal accomplishment were significantly correlated with this behavior.